Applications Of Diophantine Equations In Chemical Reactions And Cryptography - et. al., R. Radha, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper is concerned with practical applications of Diophantine equations and is intended for all readers interested in applied mathematics. We briefly explain an idea of encryption in Caesar ciphering in cryptography. Linear Diophantine equations are used to solve the chemical equations.